Beliefs around childhood vaccines in the United States: A systematic review. Issue 45 (23rd October 2019) - Gidengil, Courtney; Chen, Christine; Parker, Andrew M.; Nowak, Sarah; Matthews, Luke
Highlights: Few studies elicited the public's vaccine beliefs using open-ended questions. Concerns about vaccine safety are the most commonly stated beliefs. Mistrust in physicians, pharma, and the government may exacerbate hesitancy. The majority of studies (57%) focused on HPV vaccines. Nearly a third of the studies exclusively examined Latinos and African Americans. Abstract: Background: While childhood vaccines are safe and effective, some parents remain hesitant to vaccinate their children, which has led to outbreaks of vaccine preventable diseases. The goal of this systematic review was to identify and summarize the range of beliefs around childhood vaccines elicited using open-ended questions, which are better suited for discovering beliefs compared to closed-ended questions. Methods: PubMed, Embase, and PsycINFO were searched using keywords for childhood vaccines, decision makers, beliefs, and attitudes to identify studies that collected primary data using a variety of open-ended questions regarding routine childhood vaccine beliefs in the United States. Study designs, population characteristics, vaccine types, and vaccine beliefs were abstracted. We conducted a qualitative analysis to conceptualize beliefs into themes and generated descriptive statistics. Results: Of 1727 studies identified, 71 were included, focusing largely on parents (including in general, and those who were vaccine hesitant or at risk of hesitancy). Seven themes emerged: Adverse effects was most prominent, followed by mistrust, perceived lack of necessity, pro-vaccine opinions, skepticism about effectiveness, desire for autonomy, and morality concerns . The most commonly described beliefs included that vaccines can cause illnesses; a child's immune system can be overwhelmed if receiving too many vaccines at once; vaccines contain harmful ingredients; younger children are more susceptible to vaccine adverse events; the purpose of vaccines is profit-making; and naturally developed immunity is better than that acquired from vaccines. Nearly a third of the studies exclusively assessed minority populations, and more than half of the studies examined beliefs only regarding HPV vaccine. Conclusions: Few studies used open-ended questions to elicit beliefs about vaccines. Many of the studies that did so, focused on HPV vaccine. Concerns about vaccine safety were the most commonly stated beliefs about childhood vaccines, likely because studies were designed to capture barriers and challenges to vaccination.